Creating Social Harmony With the Bissu Community in Tiba Sebelum Berangkat Novel by Faisal Oddang and Calabai Novel by Pepi Al-Bayqunie - Venty Saskia Rohmalita; Taufik Dermawan; Nita Widiati (RIRAI Publisher, 2023)
Research about the Bissu community has been carried out in various writings and forms. Research that related to the existence, role, and gender of Bissu has been done by Muh. Saidi with the title Peran Bissu Dalam Masyarakat Bugis in 2016, while research that related to social harmony has been done by Rayi Oktafiani Utomo with the title Telaah Nilai Toleransi Dalam Novel Karya Ahmad Tohari in 2020. This study was aimed to discussed about Bissu's social harmony in Tiba Sebelum Berangkat Novel by Faisal Oddang and Calabai novel by Pepi Al-Bayqunie so that quotes, dialogues, monologues, and discourses that contained in the both novel would be primary data sources meanwhile the literature also reliable sources from the internet would be the secondary data in this research. This research was descriptive qualitative. Qualitative descriptive was done by combining the overall content analysis and interpretation in the form of a description, then the tools to analysis the data was sociology of literature. Social harmony and the role of the Bissu as local culture preservers are part of the social process, so it would be appropriate to use the theory of the sociology of literature. This research then focuses on how the Bissu community utilizes ancient religious teachings, magic, and their role as leaders of the ancient Bugis religion to create social harmony. Thus, this research will produce additional treasures in the form of writings on identity and social harmony that are carried out uniquely by the Bissu community.